Islamic Economic Analysis Reviews: The Practice of Transparency of Effective Flat Banking Installment Systems - Rahma Yudi Astuti (Al Tijarah, 2018)
This paper is motivated by the existence of customers who do not understand the installment system that should be explained by the bank when offering their products. While the delivery of product information in which there is an installment system (flat effective), the bank takes profits in advance from the customer. This will be aggravated when the customer repays the smoothly and regularly loan installment, the bank will renew the credit again by increasing the number of new credit where the principal loan will be given by the bank, which means the customer will receive a new installment schedule with the composition of loan interest greater at the beginning. The purpose of this study is to find out how the application of the principle of transparency and its obstacle factors in implementing Bank Indonesia regulation Number: 7/6 / PBI / 2005 concerning transparency of bank product information. This study is a qualitative research with a normative evaluative approach. The study indicates that transparency of using the installment system to the customer is very important because the customer will know their rights and obligations while they are taking flat installment system. This is because most customers do not know the benefit of effective flat installment system. An effective, transparency flat installment to customers is very important to prevent misunderstandings that can cause harm to both parties especially to customers.